A Review of Advanced Composite and Nanostructured Coatings by Solid-State Cold Spraying Process. Issue 2 (4th March 2019) - Li, Wenya; Assadi, Hamid; Gaertner, Frank; Yin, Shuo
ABSTRACT: Cold spraying (CS) has been widely explored over the last decade due to its low process temperature and limited thermal effect on spray materials. As a solid-state process, the inherent deficiencies of traditional thermal spraying such as oxidation, decomposition, and grain growth are avoided. This article summarizes the research work on the fabrication of composites and nanostructured coatings by the promising CS process. After a brief introduction to CS and its deposition mechanisms, the preparation methods of spray powders are classified. Different methods are appropriate for particles of various properties, and the tendency is to design composite powders by combined methods in order to create coatings with specified properties. Then, the co-deposition mechanism of composite particles as well as research findings on metal–metal, metal–ceramic, and metal–intermetallic composite coatings are reviewed concerning the deposition characteristics, microstructure and its relation to properties. Moreover, CS has been used to deposit a variety of nanostructured materials, including metals, metal–ceramic composites, and even ceramics, retaining their nanocrystalline nature in the coating without grain growth or phase transformation. Finally, the potential applications of CS and issues to be addressed in coating deposition are discussed.